1994
DOI: 10.1037/0022-3514.66.4.712
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in intraperson variability in mood.

Abstract: The experience sampling method and palm-top computers were used to obtain 75-100 randomly timed in situ assessments of 11 mood-related items from 54 Ss over 12-14 days. The variability in the distribution of an S's responses to each item was used as an estimate of intrasubject mood variability. Mood variability was stable across time (average r > .58) and across situations (average r = .51). The intercorrelations among the individual item variabilities were also substantial (average r = .41); when the items we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 35 publications
3
82
0
1
Order By: Relevance
“…Affect variability was measured in two ways. First, similar to previous research (e.g., Larsen & Diener, 1987;Penner, Shiffman, Paty, & Fritzsche, 1994), we calculated the within-person standard deviation of each emotion, which reflects the average magnitude of variation a person exhibits in affect over time. As reported in Dizén and Berenbaum (2011, Study 2), we calculated composite positive and negative affect variability scores, as discrete positive and negative variability scores were highly correlated (Cronbach's alphas 0.88, .89).…”
Section: Emotional Claritymentioning
confidence: 99%
“…Affect variability was measured in two ways. First, similar to previous research (e.g., Larsen & Diener, 1987;Penner, Shiffman, Paty, & Fritzsche, 1994), we calculated the within-person standard deviation of each emotion, which reflects the average magnitude of variation a person exhibits in affect over time. As reported in Dizén and Berenbaum (2011, Study 2), we calculated composite positive and negative affect variability scores, as discrete positive and negative variability scores were highly correlated (Cronbach's alphas 0.88, .89).…”
Section: Emotional Claritymentioning
confidence: 99%
“…Specifically, in accordance with the idea that variability represents a trait-like individual difference (e.g., Cattell, 1973;Fiske, 1961;Murray, 1938), individuals' levels of variability in surface acting and deep acting should be somewhat stable across situations and over time, with some individuals demonstrating variability and other individuals demonstrating stability, both on a regular basis. On this point, the literature on affect variability has shown that individuals possess different patterns of affective fluctuation, and these patterns are, in fact, relatively stable over time (e.g., Fleeson, 2001;Larsen, 1987;Penner, Shiffman, Paty, & Fritzsche, 1994). Indeed, the dispositional nature of affect variability is directly acknowledged in Eysenck and Eysenck's (1985) personality theory, which stipulates that variability in the experience of emotions (especially negative emotions) is a hallmark of neuroticism (see also Eid & Diener, 1999).…”
Section: Defining Emotional Labor Variabilitymentioning
confidence: 99%
“…However, it has been suggested that intra-person mood variability is predictable, and should not be attributed to the change in the situations individuals encounter (Penner et al, 1994). An individual who experiences an event that causes a negative discrepancy between the rate of perceived progress and the internal standard for progress toward the goal will tend to react in a similar way, regardless of the event causing the actual discrepancy.…”
Section: Mood Theory Mood Changes Over Time and Mood-regulationmentioning
confidence: 99%
“…To obtain a sufficient range of scores, data are needed from approximately ten different competitions. Identification of the variation in mood scores is important (Penner et al, 1994). An alternative method of developing an individualised mood profile for best and worst performance is to assess mood retrospectively.…”
Section: A Model For Mood Profilingmentioning
confidence: 99%